Myocardial Tissue Caveolae. Issue 2 (16th March 2015) - Sanon, Vani P.; Sawaki, Daigo; Mjaatvedt, Corey H.; Jourdan‐Le Saux, Claude
ABSTRACT: Caveolae and their coat proteins, caveolins (Cav), are cave‐like invaginations found in the plasma membrane of a variety of cells. These unique vesicles and their coat proteins, Cavs, have diverse effects on endothelial function, nitric oxide synthesis regulation, signal transduction, cholesterol metabolism, and apoptosis. Animal studies in Cav knockout mice demonstrate the vital role of these structural proteins on endothelial and vascular function. Genetic studies have proposed that beside neoplasia, Cavs may play a role in the development of atherosclerosis, cardiomyopathy, long QT syndrome, pulmonary fibrosis, and muscular dystrophy. The role of Cav expression in atherosclerotic disease is poorly understood and remains controversial. Interestingly, there is emerging evidence between low Cav‐1 levels and the vulnerable plaque, which could potentially identify Cav‐1 as a novel plaque biomarker. Cavs, through intricate biochemical pathways involving endothelial nitric oxide synthase and mitogen‐activated protein kinase, are known to affect the cardiovascular system at multiple levels. In the present review, we aim to highlight the nature and types of caveolae, caveolar signaling mechanisms and regulation, and the pathophysiology of Cavs as it pertains to the cardiovascular system. Ongoing research is needed to clarify the diagnostic and prognostic role of these novel proteins and to determine how the effects of Cavs can translate into clinical medicine. © 2015 American Physiological Society. Compr Physiol 5:871‐886, 2015.